Factors influencing the mutual-support willingness and needs among the rural elderly in Hunan Province, China: a cross-sectional study - Ke-ru Yao; Xin-hong Yin; Qin Luo; Xi Tang; Xiu-zhu Tan (BMC, 2022)
Abstract Background This study aimed to assess the influence factors of the mutual-support willingness and identify the mutual-support needs of elderly living in rural areas of Hunan Province, China. Methods Using the Chi-square test and logistic regression to analyze factors influencing Participants' mutual-support willingness and needs. Results Factors influencing the mutual-support willingness and needs included individual characteristics, family environment, and so on. And the rural elderly's demand for mutual-support is at a relatively high level. The total score for social support for the aged was 36.944 ± 6.487, at a moderate level. Conclusions It is necessary to objectively evaluate the factors related to mutual-support willingness and needs and take steps to enhance social support and meet elderly the needs of mutual-support, which is of great significance for improving the happiness of the elderly in their later years and alleviating the crisis of population aging in China.